Natural near field coupled leaky-mode resonant anti-reflection structures: the setae of Cataglyphis bombycina - Schwind, Bertram; Wu, Xia; Tiemann, Michael; Fabritius, Helge-Otto (Frontiers in Physics, 2024)
Leaky mode resonances of the setae of Cataglyphis bombycina are found to enhance the thermal emission of the animals by near field coupling to the chitinous exoskeleton. This is remarkable, as the setae are also an adaption to enhance the reflectivity in the visible light. Both effects are dependent on morphology, dimensions and spatial arrangement. These parameters were experimentally characterized and simulated by finite difference time domain simulations to elucidate the optical impact of the setae in the mid infrared range and the contribution of leaky mode resonances. This mode of action and the setae's optical properties in the visible range explain evolutionary strains that led to the actual morphology and size of the setae.